ENHANCING WRITING PROFICIENCY: LEARNER AUTONOMY IN CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) (CAHIERS MAGELLANES-NS, 2024)
This study explores the impact of learner autonomy on enhancing writing proficiency in the Content and Language Integrated Learning (CLIL) approach. The fundamental aim of education is to cultivate the ability to make informed decisions independently, emphasizing the learning process alongside content acquisition. CLIL offers a robust framework for fostering learner autonomy, where students actively participate in planning, executing, evaluating, and reflecting on their learning activities. Autonomous learners typically exhibit high motivation, curiosity, technological proficiency, and self-confidence. The teacher's role in this context evolves into that of a facilitator, motivator, and resource provider, creating an environment conducive to independent learning. To investigate the effectiveness of this approach, a quantitative data was collected through pre- and post-tests to measure writing proficiency improvements, while qualitative data were gathered via student interviews, classroom observations, and questionnaires to understand the development of learner autonomy. The study involved a control group and an experimental group, each comprising 50 students. The experimental group was exposed to the CLIL framework with a focus on learner autonomy, while the control group followed a traditional language learning curriculum. This paper underscores the efficacy of integrating learner autonomy with CLIL to enhance writing skills, offering valuable insights for educators aiming to foster independent learning capabilities in their students.